Language Shifts in Folkative Instagram Comments - Koemba, Fitriani Putri; Rajeg, Gede Primahadi Wijay; Ediwan, I Nyoman Tri (Apollo Project: Jurnal Ilmiah Program Studi Sastra Inggris, 2025)
Social media nowadays presents a venue for speakers to convey messages in different languages. This study aims at identifying the factors of language shift in social media comments for bilingual, multimodal content posted on an Instagram account, called Folkatives. The analysis was based on two data types, namely verbal (English) and visual (Indonesia) data from the post and questionnaire data. They are analyzed with reference to Holmes’ (2001) theory on the factors of language shift. The results of this study indicate there are three factors of language shift in the two comments with the most likes in every six Folkative posts on April 30, 2022. Based on the analysis of the data (comments) and the results of the questionnaire on twelve Folkative followers, it was found that a language shift occurred due to social factors, the economy, and demography. his can be reviewed further because social media is a form of internet communication that continues to grow and will not die in the social world. Keywords: Language shift, Instagram, Folkative, Verbal, Visual